Promoting labour relations stability under company law: a critical analysis of internal corporate social responsibility in South Africa - Maphiri, Mikovhe (Department of Commercial Law, 2023)
Traditionally, companies have viewed aspects relating to employees' needs and interests as falling within the domain of labour law, collective bargaining and the contract of employment. This approach has prevailed throughout decades of labour strife and unrest, as the adversarial nature of labour law in South Africa and the political history of the country have influenced the management of labour relations. In essence, labour law in all its facets has not succeeded in providing effective channels for worker participation and much-needed employee engagement in the workplace, and ultimately this failure has exacerbated instability in the labour relations environment. The thesis argues for a complementary channel for worker participation and for a collaborative approach to be adopted by company law and labour law, envisaged through internal corporate social responsibility (internal CSR). In this regard, and against the backdrop of the unrest in the mining industry, the thesis examines the potential of the provisions of s 72(4) of the Companies Act 71 of 2008 (the Companies Act), read with reg 43 of the Companies Regulations, 2011, as a potential conduit for the promotion of labour relations stability through internal CSR under company law. The thesis provides an in-depth evaluation of the different approaches to corporate governance and an examination of the composition, mandate and structuring of the s 72(4) social and ethics committee as a potential platform for promoting labour stability through internal CSR. An argument is made for the use of the social and ethics committee as a platform for internal CSR to promote much-needed employee engagement. The arrangements would not overlap with trade union activities, nor would they replace workplace forums (which in any event have not functioned as intended and the legislative framework probably needs revising), nor do the arrangements place fiduciary obligations on employees. Moreover, the potential for employee voice through the committee is likely to promote much-needed engagement on labour issues, and this could be achieved through collaboration between company law and labour law. The thesis recommends amendments to the Companies Act and the Companies Regulations that will allow for the promotion of internal CSR for labour stability under company law.